(untitled) (Al-Mansour Journal, 2022)
In this investigation, a three-dimensional finite element model has beenn used to analyze four concrete-filled fiber reinforced polymer (FRP) tubes and two fiber-wrapped concrete columns under sustained axial compressive load utilizing ANSYS software. Twenty-node viscoelastic element has been used to model the concrete, while the FRP tube is modeled using twenty-node isoparametric solid element and fiber-wrap is modeled using eight-node isoparametric shell element, both connected by eight-node isoparametric interface element. Also, the effects of some important parameters including concrete compressive strength, tube wall thickness, number of fiber-wraps, column diameter, ultimate creep coefficient, and type of FRP on the creep behavior of these columns have been investigated. Comparison between the numerical and available experimental long-term results showed good agreement with a maximum difference of the total strain values of 5.5%, which confirms the accuracy and validity of the models and materials constitutive relations and method used. The numerical results also showed that a stress transfer in the concrete-filled FRP column occurred with time between the FRP tube and the concrete, leading to a 22% stress reduction in the concrete and a stress increase in the FRP of 25% after 200 days of loading.